Urinary aHGF, IGFBP3 and OPN as diagnostic and prognostic biomarkers for prostate cancer. (December 2013) - Prager, Alisa J; Peng, Cynthia R; Lita, Elena; McNally, Debbie; Kaushal, Aradhana; Sproull, Mary; Compton, Kathryn; Dahut, William L; Figg, William D; Citrin, Deborah; Camphausen, Kevin A
Aim: Serum PSA screening for prostate cancer (PCa) is controversial. Here, we identify three urinary biomarkers – a HGF, IGFBP3 and OPN – for PCa screening and prognostication.Methods: Urinary a HGF, OPN and IGFBP3 from healthy men (n = 19) and men with localized (n = 65) and metastatic (n = 36) PCa were quantified via ELISA. Mann–Whitney nonparametric t-test and the Search Tool for the Retrieval of Interacting Genes/Proteins (STRING) analyses were used to analyze associations.Results: Mean a HGF and IGFBP3 levels were significantly elevated in PCa patients versus controls (p = 0.0006 and p = 0.0012, respectively), and the area under the curve of the receiver operating characteristic curve (indicator of diagnostic accuracy) for a HGF and IGFBP3 was 0.75 and 0.74, respectively. OPN levels were significantly higher in metastatic groups (p = 0.0060) versus localized and controls (area under the curve = 0.68).Conclusion: Urinary a HGF and IGFBP3 exhibit the capacity for diagnostic discrimination for PCa, whereas OPN may indicate presence of metastatic disease.